Phytodiversity in Beeshazar Lake and Surrounding Landscape System - Jha, Sasinath (Our Nature, 2008)
This paper deals in general with diversity of vascular plants, status of invasive alien species (IAS) and nationally threatened plant species, human use potentials of phytodiversity, and some phytodiversity-based measures to restore and improve the Ramsar characteristics of Beeshazar Lake and surrounding landscape system, which isa part of the Barandabhar forest corridor (BFC) - an extension of buffer zone of the Chitwan National Park, Nepal. Keywords: Phytodiversity, Beeshazar Lake doi:10.3126/on.v5i1.797 Our Nature (2007)5:41-51